Susceptibility of hepatic tissue of Iberian pigs is enhanced by free-range feeding and reduced by vitamin E supplementation - López Bote, C. J.; Rey, A. I. (Nutrition Research, 2001)
The effect of feeding system (free-range vs conﬁnement) and the supplementation of concentrated feed with vitamin E and copper was investigated. Dietary copper supplementation (100 mg/kg) increased the hepatic concentration of copper in hepatic tissue (P , 0.05), reaching similar concentrations than pigs fed under free-range conditions. Free-range feeding produced higher concentration of a-tocopherol than those from pigs fed in conﬁnement with the basal level of vitamin E, but lower values than pigs fed supplemented levels, which may be attributed to the relative high concentration of a-tocopherol in the grass. Liver samples from pigs under free-range conditions showed higher susceptibility to lipid oxidation than pigs produced in conﬁnement and fed mixed diets. No signiﬁcant effect of copper was observed in hepatic tissue oxidation, but vitamin E supplementation markedly decreased oxidation
Keywords: a-tocopherol; copper; fatty acid; liver; pig